Theory Acceptance Model (TAM) untuk Mengukur Minat Wanita dalam Mengikuti Pelatihan Prakerja - Solehatin Ika Putri; Lina Affifatusholihah; Farah Putri Wenang Lusianingrum (Universitas Batanghari, 2023)
This study intends to obtain the impact of perceived usefulness, perceived ease of use and culture factor to women interest to take a part in pre – employment online training. This study used a quantitative approach and analysis used in this study is SEM Warp PLS 6.0 by collecting data to 300 sample by purposive sampling method. This study adopted Technology Acceptance Model by Fred Davis used perceived usefulness and perceived ease of use variable and collaborate culture factor as novelty. The findings in this study indicate that perceived usefulness, perceived ease of use, and culture factor in a partial and simultaneous impacted to women interest to take a part in pre – employment online training in Serang City.